The Use of Drill Method in Improving the Ability to brush Teeth Self-help for Students with Intellectual Disabilities - Marliana, Intan Maharani Dian; Supriyadi, Agus (Universitas Pendidikan Indonesia (UPI), 2021)
The purpose of this study was to determine the use of the drill method in improving the ability to brush teeth for students with intellectual disabilities. The method used is the method of demonstration, assignment, and question, and answer. The subjects of this study were 2 students with intellectual disabilities at the Special School in Tasikmalaya, West Java. The results of the study showed the development of student's abilities, which can be seen from the changes in students' scores increase. The score obtained by D in the initial ability is 40 with a percentage of 50% to 75 with a percentage of 93.75% there is an increase of 43.75% and the score obtained by E in the initial ability is 20 with a percentage of 25% to 61 with a percentage of 76.25% there was an increase of 51.25%. That's because using the drill method makes it easier for students to understand the procedure for brushing teeth. Students with intellectual disabilities need repeated learning to become a habit. The use of methods that suit the needs of students can help students to more easily understand learning materials, especially students with intellectual disabilities. The drilling method can be considered by teachers to be used in the self-help learning process, especially brushing teeth for students with intellectual disabilities, and can be developed for learning other materials.